Preserving heritage: An assessment of traditional rice (Oryza sativa) varieties and production patterns in the Someshwar valley, Almora - PANDEY, BHAWNA; CHANDRA, NAVEEN; UPADHYAY, M L; Arya, Dhani (The Indian Journal of Agricultural Sciences, 2026)
The present study was carried out during the rainy (kharif) season of 2024 to document the diversity, production trends, and drivers of change affecting traditional rice varieties in the Someshwar valley of Almora district, Uttarakhand. Field-based surveys were conducted across six villages using structured questionnaires and interviews. Twelve traditional rice varieties were recorded, exhibiting distinct ecological adaptability, end-use values, and cultural significance. Comparative production analysis between 1990–2000 and 2010–2020 revealed a substantial decline in the productivity of most varieties, while three varieties were no longer recorded under active cultivation. Conversely, one variety showed a 50% increase in production, while another remained relatively stable. Questionnaire survey analysis identified climate variability, water scarcity, declining soil fertility, increased pest incidence, labour shortages due to rural out-migration, and rising human-wildlife conflict as the primary drivers of these changes. The study highlights the urgent need for integrated conservation strategies to safeguard traditional rice germplasm. These strategies should encompass both in situ and ex situ conservation approaches, while simultaneously enhancing the ecological resilience and economic sustainability of traditional farming systems. Promoting the cultivation of locally adapted varieties, improving pest and water management techniques, and strengthening extension services through farmer education, training, and incentives are essential components of a sustainable agricultural revitalisation strategy. Additionally, promoting value addition, advancing women’s empowerment, and strengthening socio-economic resilience and market access are vital for the comprehensive development of rice-farming communities. By advancing agricultural systems that are both ecologically sustainable and economically viable, it is possible to ensure long-term food security, cultural heritage preservation, and the livelihood resilience of farming communities in the Himalayan region.